(untitled) (Conferencea, 2022)
Through this article, we will show how important or insignificant the role of international observers is in the electoral process in our country, as well as review the recommendations set out in their special reports and try to show how involved they are in electoral legislation. We will also indicate whether the recommendations and suggestions made by them are binding.